Association Between Plasma ADAMTS-7 Levels and Diastolic Dysfunction in Patients with Type 2 Diabetes Mellitus - Asimina Ganotopoulou; Emmanouil Korakas; Loukia Pliouta; Aikaterini Kountouri; Sotirios Pililis; Stamatios Lampsas; Ignatios Ikonomidis; Loukianos S. Rallidis; Athanasia Papazafiropoulou; Andreas Melidonis; Vaia Lambadiari (Medicina)
A disintegrin and metalloproteinase with thrombospondin motifs-7 (ADAMTS-7) belongs to the family of metalloproteinases that contributes to tissue homeostasis during morphogenesis and reproduction. These metalloproteinases regulate various cell functions such as cell proliferation, are important regulators in tissue regeneration, and play a role in vascular remodelling, which is involved in atherosclerosis development. Despite the well-established association between ADAMTS-7 and atherosclerotic disease, data regarding the metalloproteinase’s association with LV function remain scarce. The aim of this study was to investigate the association of ADAMTS-7 levels with diastolic dysfunction and various echocardiographic parameters in patients with type 2 diabetes mellitus. All patients underwent a clinical, vascular, and echocardiographic examination during their visit. Plasma ADAMTS-7 levels were measured in all patients. The results showed that diastolic dysfunction was strongly associated with age, but had no statistically significant association with ADAMTS-7. When individual echocardiographic parameters were examined, ADAMTS-7 levels showed a positive tendency only with deceleration time (DT), with the other echocardiographic parameters being positively associated only with age. The possible role of ADAMTS-7 in diastolic dysfunction and in the development and progression of heart failure in patients with type 2 diabetes mellitus deserves further investigation.